2021
DOI: 10.1111/ijfs.14983
|View full text |Cite
|
Sign up to set email alerts
|

Oyster hydrolysate ameliorates ethanol diet‐induced alcoholic fatty liver by regulating lipid metabolism in rats

Abstract: We evaluated the effect of oyster hydrolysate, which was prepared using transglutaminase, protamex and neutrase (TGPN), on alcoholic fatty liver. Sprague-Dawley rats were fed a diet containing 5% (v/v) ethanol or an isocaloric amount of dextrin-maltose for 6 weeks and orally administered TGPN or silymarin for another 4 weeks. TGPN significantly decreased the liver index (liver weight/body weight), serum and hepatic lipid levels and increased the serum adiponectin level. Based on histological analysis, TGPN red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…YA was released from oysters by enzymatic hydrolysis. Our previous studies demonstrated that OH produced by in vitro enzymatic hydrolysis of oysters contained various bioactive peptides such as TAY, VK, KY, FYN, and YA and displayed antihypertensive, anti-inflammatory, antidiabetic, antioxidative, and hepatoprotective effects in in vitro and in vivo tests [24,25,[45][46][47]. YA can be a bioactive peptide.…”
Section: Discussionmentioning
confidence: 99%
“…YA was released from oysters by enzymatic hydrolysis. Our previous studies demonstrated that OH produced by in vitro enzymatic hydrolysis of oysters contained various bioactive peptides such as TAY, VK, KY, FYN, and YA and displayed antihypertensive, anti-inflammatory, antidiabetic, antioxidative, and hepatoprotective effects in in vitro and in vivo tests [24,25,[45][46][47]. YA can be a bioactive peptide.…”
Section: Discussionmentioning
confidence: 99%